Cave discoveries and speleogenetic features in northeast Greenland - Moseley, GE; Barton, HA; Spötl, C; Töchterle, P; Paul Smith, M; Bjerkenås, SE; Blakeley, C; Hodkinson, PD; Shone, RC; Sivertsen, HC; Wright, M (British Cave Research Association, 2020)
Solution caves situated in the Centrumsø region of northeast Greenland (80°N) were first documented in 1960. Since then, there have been three dedicated caving expeditions to the area that have increased the numbers of cave observations and discoveries substantially. Here, the larger caves, as documented by the Greenland Caves Project during 2015 and 2019, are presented, including surveys and summaries of their key features. Additionally, smaller caves and potential leads, as documented during 2019, are also presented.